2020
DOI: 10.1038/s41598-020-59914-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lower Extremity Skeletal Muscle Mass and Impaired Cognitive Function in Type 2 Diabetes

Abstract: Lower extremity skeletal muscle mass (LESM) in Type 2 Diabetes (T2D) has been linked to adverse clinical events, but it is not known whether it is associated with cognitive difficulties. We conducted a cross-sectional study on 1,235 people (mean age 61.4 ± 8.0 years) with T2D under primary and secondary care in Singapore. Bioelectrical impedance analyses (BIA) measures of upper extremity skeletal muscle mass (UESM), LESM and appendicular skeletal muscle index (SMI) were related to the Repeatable Battery for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Similarly, sarcopenia is common among dementia patients [ 12 ]. The shared pathophysiological mechanisms and pathways between sarcopenia and cognitive impairment involve oxidative stress, chronic inflammation, hormonal changes, insulin resistance, and the gut microbiota [ 11 , 22 , 23 ]. Thus, the relationship between sarcopenia and cognitive impairment is complex and mediated by various internal and external factors, among which nutrition may be a major contributor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sarcopenia is common among dementia patients [ 12 ]. The shared pathophysiological mechanisms and pathways between sarcopenia and cognitive impairment involve oxidative stress, chronic inflammation, hormonal changes, insulin resistance, and the gut microbiota [ 11 , 22 , 23 ]. Thus, the relationship between sarcopenia and cognitive impairment is complex and mediated by various internal and external factors, among which nutrition may be a major contributor.…”
Section: Discussionmentioning
confidence: 99%
“…But another study found that there was no significant correlation between upper muscle strength and cognitive function in Type 2 diabetes. 5 The different results may be due to the specificity of the population, the results of our study need to be validated in other populations in the future. Multiple potential explanations for the observed association between poor physical performance and cognitive impairment exist.…”
Section: Correlation Between Physical Performance and Cognitive Functionmentioning
confidence: 91%
“…Individuals were included as following criteria: 4 (1) Older adults people ≥65 years old; (2) Have lived in the community for at least one year; (3) Willing to participate in this study. Exclusion criteria: 4 (1) General cognitive function was assessed using the Chinese version of the Matisse Dementia Rating Scale (CDRS), excluding participants who already had severe cognitive impairment and dementia or other neurodegenerative diseases; (2) those who could not take care of themselves and the instrumental activities of daily living scale were more than or equal to three items that could not be completed and could not walk independently; (3) people with hearing impairment, visual impairment and communication difficulties; (4) those who took sedatives in the last one or two months; (5) unable to perform the physical performance test. The methodological sessions were carried out in accordance with the approved guidelines and regulations.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…15 Indeed, a recent study reported the association between lower, but not upper, extremity muscle mass and cognitive impairment in persons with type 2 diabetes. 35 More studies can elucidate the relationship between specific cognitive domains and gait. Taken together, lower-extremity strength and cognition, both domains of intrinsic capacity, 36 are important factors in sarcopenia prevention.…”
Section: Factors Associated With Sarcopeniamentioning
confidence: 99%